2016
DOI: 10.1111/pcn.12430
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline combination therapy with fluvoxamine in moderate‐to‐severe obsessive–compulsive disorder: A placebo‐controlled, double‐blind, randomized trial

Abstract: The results of this study suggest that minocycline could be a tolerable and effective adjuvant in the management of patients with OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…These results are consistent with the cytokine levels found in OCD patients, as activated microglia produce IL-6, IL-1β, and TNF-α [11,181]. This could explain the effectiveness of minocycline, which reduces microglia activation [185], as another OCD treatment in Reference [137], and highlights the importance for precision medicine to consider immunological etiological factors.…”
Section: Conclusion: Future Lines Of Research For Etiological Immsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with the cytokine levels found in OCD patients, as activated microglia produce IL-6, IL-1β, and TNF-α [11,181]. This could explain the effectiveness of minocycline, which reduces microglia activation [185], as another OCD treatment in Reference [137], and highlights the importance for precision medicine to consider immunological etiological factors.…”
Section: Conclusion: Future Lines Of Research For Etiological Immsupporting
confidence: 82%
“…Minocycline, a specific antibiotic, is particularly interesting because of its action on microglia (see below). Minocycline was studied as a potential new pharmacological treatment for OCD, and the results were mixed: one study found that minocycline could be a good adjunctive treatment to classical OCD treatment with SSRIs [137], but another one did not find this result [138] (Table 5). Another antibiotic, cefdinir, was studied, but it showed no effectiveness on the CY-BOCS scores when compared to a placebo [171].…”
Section: Alternative Treatments For Ocdmentioning
confidence: 99%
“…Of these patients, 7 were also taking concurrent medications (4 patients were taking brotizolam, and 3 were taking other benzodiazepines), and 2 were medicated with low dosages (100-150 mg) of sulpiride only between T1 and T2. All of the patients were screened with the DSM-IV criteria for a unipolar MDD diagnosis, using the Mini-International Neuropsychiatric Structural Interview (MINI) [16,17]. No patient had current or past bipolar disorder or schizophrenia episodes.…”
Section: Methodsmentioning
confidence: 99%
“…In animals, altered anxiety‐related social behaviors have been observed and associated with amygdala hyperactivity (implicated in ASD and social anxiety disorder; Stilling et al, ). Potential therapeutic benefits of antibiotics have also been observed in psychiatric conditions including ASD (Sandler et al, ), OCD (Esalatmanesh et al, ; Rodriguez et al, ), and depression (Miyaoka et al, ; Molina‐Hernández, Tellez‐Alcántara, Pérez‐García, Olivera‐Lopez, & Jaramillo‐Jaimes, ). However, previous antibiotic exposure has also been associated with risk for anxiety and depression (Köhler‐Forsberg et al, ; Lurie, Yang, Haynes, Mamtani, & Boursi, ).…”
Section: What Can Alter the Gut Microbiome?mentioning
confidence: 99%